The Second Study of Clinical and Immunological Findings in Anti-laminin 332-Type Mucous Membrane Pemphigoid Examined at Kurume University—Diagnosis Criteria Suggested by Summary of 133 Cases - Qian, Hua; Natsuaki, Yohei; Koga, Hiroshi; Kawakami, Tamihiro; Tateishi, Chiharu; Tsuruta, Daisuke; Ishii, Norito; Li, Xiaoguang; Hashimoto, Takashi (Frontiers in Immunology, 2021)
Background Recently, we published an article retrospectively summarizing the results in 55 anti-laminin 332 (LM332)-type mucous membrane pemphigoid (MMP) cases examined at Kurume University, which were diagnosed by strict inclusion criteria, including positive reactivity in direct immunofluorescence and absence of antibodies to non-LM332 autoantigens. However, indirect immunofluorescence using 1M-NaCl-split normal human skin (ssIIF) is also valuable for diagnosis of anti-LM332-type MMP. Methods In this second study, we selected 133 anti-LM332-type MMP cases, which were diagnosed by our different inclusion criteria: (i) immunoglobulin G (IgG) deposition to basement membrane zone (BMZ) by direct immunofluorescence or IgG reactivity with dermal side of split skin by ssIIF, (ii) positivity for at least one of the three subunits of LM332 by immunoblotting of purified human LM332, and (iii) the presence of mucosal lesions. Clinical, histopathological, and immunological findings were summarized and analyzed statistically. Although these cases included the 55 previous cases, the more detailed study for larger scale of patients was conducted for further characterization. Results Clinically, among the 133 patients, 89% and 43% patients had oral and ocular mucosal lesions, respectively, 71% had cutaneous lesions, and 17% had associated malignancies. Histopathologically, 93% patients showed subepidermal blisters. The sensitivities of ssIIF and direct immunofluorescence are similar but are significantly higher than indirect immunofluorescence using non-split human skin (both p < 0.001). In immunoblotting of purified LM332, patient IgG antibodies most frequently reacted with LMγ2 subunit (58%), followed by LMα3 (49%) and LMβ3 (36%). Thirty-four percent patients recognized additional non-LM332 autoantigens. Statistical analysis revealed that autoantibodies against non-LM332 autoantigens might stimulate the production of anti-LMγ2 antibodies. Conclusions This retrospective study further characterized in more detail the clinical and immunological features of 133 cases of anti-LM332-type MMP, in which the new diagnostic criteria without positive direct immunofluorescence reactivity were useful for the diagnosis. Higher frequency with anti-LMγ2 antibodies suggested more significant pathogenic role of this subunit. Additional autoantibodies to non-LM332 autoantigens detected in one-third of the patients may contribute to complexity in anti-LM332-type MMP, including the induction of anti-LMγ2 antibodies.